HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP DENGAN PEMANFAATAN PELAYANAN POSYANDU LANSIA DI LEMBANG PAONGANAN KECAMATAN BUNTU PEPASAN - Widia Axselya Palungan; Christian Bertom Pajung; Prycilia P. Mamuaja (Yayasan Syalom Cipta Sumikolah, 2024)
Elderly Age is the final stage of the aging process. The elderly are individuals aged 60 and above. This study aims to determine the relationship between knowledge and attitude with the utilization of elderly health services at the Posyandu (Integrated Health Post) in Lembang Paonganan, Buntu Pepasan District. This research employs an observational analysis approach with a cross-sectional design. A sample of 53 people was selected using stratified random sampling. The independent variables in this study are knowledge and attitude, while the dependent variable is the utilization of elderly health services at the Posyandu. Based on the chi-square test results, there is a relationship between knowledge (p=0.020) and attitude (p=0.000) with the utilization of elderly health services at the Posyandu, with a significance level of α=0.05. The conclusion of this study is that there is a relationship between knowledge and attitude with the utilization of Posyandu services in Lembang Paonganan, Buntu Pepasan.